Development of a Wireless Communication Enabled Device for Monitoring Heart Rate and Body Temperature for Independent Use - La Febry Andira Rose Cynthia; Alvin Hetriawan; Fatkhur Rokhman; Muhammad Faris Pradana; Lailis Syafa’ah (Strada Journal of Pharmacy, 2024)
Human health conditions can be seen from their heart rate and body temperature. Research aims to make it easier for health workers and humans in general to know their heart rate and body temperature. Therefore, a portable heart rate monitoring device was designed that uses an IoT system. The portable design aims to make the tool practical, and the use of IoT makes it easier for health workers to see patient conditions remotely. The MAX30100 sensor is used to determine heart rate while the DS18B20 sensor is used to determine body temperature which is connected to the microcontroller. It is hoped that this research will make it easier for health workers and humans to receive immediate treatment during emergencies.